ENGLISH 3 : THE LINK BETWEEN BATES AND CORONA VIRUS AND THE CONCEPT OF EATING HALAL ANIMALS IN ISLAM - Khan, Abdur Rahman; Ahmed, Muhammad Mashhood; Yousuf Khan, Abdur Rehman (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
During the last two months, Coronaviruses (CoVs) has turned into a terrifying worldwide pandemic, which started from the Wuhan city of China. Now this virus has reached nearly the sixty countries of the world. More than 80,000 people have been infected in China only and nearly 3,000 have died from this fatal virus. It is an established fact that coronavirus outbreak originated from bats which have been sold with other wild animals in the meat market of Wuhan city. The purpose of this research study is to provide an insight on the Islamic shariah laws regarding the permissibility and impermissibility of animals found on the earth and under the sea. Our study outcomes reveal that shariah laws in this regard impart the best principles, which protect the human lives from coronavirus type outbursts. However, it is far better to acquire preliminary measures than to cure a disease through medications. Being a divine religion, Islamic teachings communicate a complete package of daily routine activities from religious deeds to consuming food. Islam is the only religion which clearly establishes rules about the concept of halal (permissible) and haram (impermissible) food and animals.